Implementation of Environmental, Social and Governance (ESG) Reporting in Public Company Financial Accounting Practices - Sambodo, Deny Purwo (Dhana, 2025)
This study aims to analyze the implementation of Environmental, Social, and Governance (ESG) reporting in the financial accounting practices of public companies in Indonesia. The focus of the study is directed at how companies integrate ESG aspects into financial reports and identify the driving factors and barriers to its implementation. The research method used is qualitative with a descriptive approach, through in-depth interviews, documentation studies, and thematic analysis of public companies that have implemented ESG reporting. The results show that most public companies in Indonesia still place ESG reporting separately in their sustainability reports and have not fully integrated it into their financial reports. The main factors driving ESG implementation include OJK regulations, global investor demands, and management awareness of business sustainability. The obstacles encountered include the lack of standard accounting standards, limited human resources, and additional reporting costs. This study emphasizes the need to develop more comprehensive accounting reporting standards so that ESG can be consistently integrated into the financial accounting practices of public companies.